Neonatal mortality of low-birth-weight infants in Bangladesh - Yasmin Sohely; Osrin David; Paul Elizabeth; Costello Anthony (The World Health Organization, 2001)
OBJECTIVE: To ascertain the role of low birth weight (LBW) in neonatal mortality in a periurban setting in Bangladesh. METHODS: LBW neonates were recruited prospectively and followed up at one month of age. The cohort of neonates were recruited after delivery in a hospital in Dhaka, Bangladesh, and 776 were successfully followed up either at home or, in the event of early death, in hospital. FINDINGS: The neonatal mortality rate (NMR) for these infants was 133 per 1000 live births (95% confidence interval: 110-159). The corresponding NMRs (and confidence intervals) for early and late neonates were 112 (91-136) and 21 (12-33) per thousand live births, respectively. The NMR for infants born after fewer than 32 weeks of gestation was 769 (563-910); and was 780 (640-885) for infants whose birth weights were under 1500g. Eighty-four per cent of neonatal deaths occurred in the first seven days; half within 48 hours. Preterm delivery was implicated in three-quarters of neonatal deaths, but was associated with only one-third of LBW neonates. CONCLUSION: Policy-relevant findings were: that LBW approximately doubles the NMR in a periurban setting in Bangladesh; that neonatal mortality tends to occur early; and that preterm delivery is the most important contributor to the NMR. The group of infants most likely to benefit from improvements in low-cost essential care for the newborn accounted for almost 61% of neonatal mortalities in the cohort.